USE OF NUTRIENT RISK IN CRITICALLY ILL SCORE TO ASSESS NUTRITIONAL RISK IN MECHANICALLY VENTILATED PATIENTS - ALI, MA; ISHTIAQ, W; DIN, SU; SAJJAD, MM; ALI, S; KHAN, J (Biological and Clinical Sciences Research Journal, 2024)
Ensuring proper nutritional support is crucial for critically ill patients. This nutritional deficit is closely associated with heightened susceptibility to nosocomial infections, delayed wound healing, and an escalated risk of mortality. Objective: The objective of this study is to evaluate the effectiveness of the Nutrient Risk in Critically Ill (NUTRIC) score in assessing the nutritional risk of mechanically ventilated patients. Method: It is a cross-sectional study. It is conducted at the Department of Critical Care Medicine, Shifa International Hospital, Islamabad from 1st Jan 2024 to 30 May 2024. The calculated sample size was 381 selected by non-probability consecutive sampling. The study utilized the modified Nutritional Risk in the Critically Ill (mNUTRIC) score to assess nutritional risk in mechanically ventilated (MV) patients. Data will be analyzed using SPSS 24.0. A P value of ≤ 5 will be significant Result: The study included a total of 381 participants, with a mean age of 55.7 ± 17.5 years and, a BMI was 23.7 ± 3.5. 219 (57.48%) had low nutritional risk (NUTRIC score ≤4), while 162 (42.51%) had high nutritional risk (NUTRIC score ≥5). Patients in the high nutritional risk group had a longer stay in the intensive care unit (ICU), had fewer ventilator-free days and had higher mortality rates compared to those in the low nutritional risk group (8.5 ± 4.1 days vs. 5.2 ± 3.9 days, p-value < 0.01). Conclusion: The study highlights the significance of the NUTRIC score as a valuable tool for the estimation of nutritional risk among mechanically ventilated patients in the ICU setting